The effects of peripheral lipoprotein metabolism on cerebrovascular inflammation in APP/PS1 mice: Molecular and cell biology/vascular factors. (7th December 2020) - Button, Emily B.; Boyce, Guilaine K.; Wilkinson, Anna; Stukas, Sophie K.; Hayat, Arooj; Cheng, Wai Hang; Wadsworth, Brennan J.; Fan, Jianjia; Robert, Jerome; Martens, Kris M.; Wellington, Cheryl L.
Abstract: Background: Although Alzheimer's disease (AD) is characterized by amyloid beta (Aβ) plaques and neurofibrillary tangles, most AD patients also exhibit cerebrovascular dysfunction. Therefore, strategies promoting cerebrovascular resilience have potential as therapeutic or preventative interventions against AD. High‐density lipoproteins (HDL) have several known beneficial functions on peripheral vessels. Further, increased plasma HDL concentrations have been associated with reduced dementia risk and HDL supplementation reduces both amyloid pathology and cognitive deficits in AD model mice. We therefore hypothesized that HDL may promote cerebrovascular health to protect against AD. We investigated the effects of HDL specifically on the cerebrovasculature in APP/PS1 mice, an AD model, using two methods. Methods: First, we reduced plasma HDL levels by creating APP/PS1 mice genetically deficient for apolipoprotein (apo)A‐I, the primary protein component of HDL. Second, we treated 12‐month old APP/PS1 mice with a non‐brain penetrant liver X receptor (LXR) agonist for seven days to selectively upregulate the HDL biogenesis pathways in peripheral tissues. We measured cognitive deficits using cued and contextual fear conditioning tests. Fluorescent amyloid staining was used to assess vascular amyloid deposition. Immunofluorescent imaging evaluating glial fibrillary acidic protein (GFAP) and intercellular adhesion molecule 1 (ICAM‐1) association with CD31 positive area was used to assess vessel‐associated astrogliosis and endothelial inflammation, respectively. Results: At 12 months of age, apoAI‐null mice had increased cognitive deficits in cued and contextual fear conditioning tests, increased vascular amyloid burden, increased vessel‐associated astrogliosis, and increased brain endothelial cell inflammation. Seven days of LXR agonist treatment had no effect on amyloid pathology or astrogliosis. However, LXR agonist‐treated APP/PS1 mice displayed reduced cognitive deficits in cued fear conditioning tests and reduced endothelial cell inflammation. Conclusions: Circulating HDL promotes cerebrovascular health in APP/PS1 mice by limiting both Aβ‐induced vascular inflammation and vascular Aβ deposition resulting in reduced amyloid pathology and cognitive deficits.